Studies of mice deleted for Sox3 and uc482: relevance to X-linked hypoparathyroidism. Issue 2 (February 2020) - Gaynor, Katherine U; Grigorieva, Irina V; Mirczuk, Samantha M; Piret, Sian E; Kooblall, Kreepa G; Stevenson, Mark; Rizzoti, Karine; Bowl, Michael R; Nesbit, M Andrew; Christie, Paul T; Fraser, William D; Hough, Tertius; et al.
Abstract : Hypoparathyroidism is genetically heterogeneous and characterized by low plasma calcium and parathyroid hormone (PTH) concentrations. X-linked hypoparathyroidism (XLHPT) in two American families is associated with interstitial deletion-insertions involving deletions of chromosome Xq27.1 downstream of SOX3 and insertions of predominantly non-coding DNA from chromosome 2p25.3. These could result in loss, gain, or movement of regulatory elements, which include ultraconserved element uc482, which could alter SOX3 expression. To investigate this, we analysed SOX3 expression in EBV-transformed lymphoblastoid cells from three affected males, three unaffected males, and four carrier females from one XLHPT family. SOX3 expression was similar in all individuals, indicating that the spatiotemporal effect of the interstitial deletion-insertion on SOX3 expression postulated to occur in developing parathyroids did not manifest in lymphoblastoids. Expression of SNTG2, which is duplicated and inserted into the X chromosome, and ATP11C, which is moved telomerically, were also similarly expressed in all individuals. Investigation of male hemizygous ( Sox3 −/Y and uc482 −/Y ) and female heterozygous ( Sox3 +/ − and uc482 +/ − ) knockout mice, together with wild-type littermates (male Sox3 +/Y and uc482 +/Y, and female Sox3 +/+ and uc482 +/+ ), revealed Sox3 −/Y, Sox3 +/ −, uc482 − /Y, and uc482 +/ − mice to have normal plasma biochemistry, compared to their respective wild-type littermates. When challenged with a low calcium diet, all mice had hypocalcaemia, and elevated plasma PTH concentrations and alkaline phosphatase activities, and Sox3 −/Y, Sox3 +/ −, uc482 −/Y, and uc482 +/ − mice had similar plasma biochemistry, compared to wild-type littermates. Thus, these results indicate that absence of Sox3 or uc482 does not cause hypoparathyroidism and that XLHPT likely reflects a more complex mechanism.